Effect of water on the electroresponsive structuring and friction in dilute and concentrated ionic liquid lubricant mixtures. Issue 48 (9th December 2020) - Pilkington, Georgia A.; Welbourn, Rebecca; Oleshkevych, Anna; Watanabe, Seiya; Pedraz, Patricia; Radiom, Milad; Glavatskih, Sergei; Rutland, Mark W.
Abstract : The influence of ambient levels of water on the electroresponsive interfacial structuring and nanofriction of ionic liquid lubricant mixtures has been investigated by neutron reflectivity and atomic force microscopy. Abstract : The effect of water on the electroactive structuring of a tribologically relevant ionic liquid (IL) when dispersed in a polar solvent has been investigated at a gold electrode interface using neutron reflectivity (NR). For all solutions studied, the addition of small amounts of water led to clear changes in electroactive structuring of the IL at the electrode interface, which was largely determined by the bulk IL concentration. At a dilute IL concentration, the presence of water gave rise to a swollen interfacial structuring, which exhibited a greater degree of electroresponsivity with applied potential compared to an equivalent dry solution. Conversely, for a concentrated IL solution, the presence of water led to an overall thinning of the interfacial region and a crowding-like structuring, within which the composition of the inner layer IL layers varied systematically with applied potential. Complementary nanotribotronic atomic force microscopy (AFM) measurements performed for the same IL concentration, in dry and ambient conditions, show that the presence of water reduces the lubricity of the IL boundary layers. However, consistent with the observed changes in the IL layers observed by NR, reversible and systematic control of the friction coefficient with applied potential was still achievable. Combined, these measurements provide valuable insight into the implications of water on the interfacial properties of ILs at electrified interfaces, which inevitably will determine their applicability in tribotronic and electrochemical contexts.